Mutagenesis selection and large-scale cultivation of non-green Chlamydomonas reinhardtii for food applications - Cao, Gang; Hu, Kun; Hu, Zhewen; Wu, Qianlong; Liu, Siyuan; Chen, Xiaoping; Meng, Xiangrui; Hu, Zhangfeng; Feng, Li (Frontiers in Nutrition, 2024)
Background The green alga Chlamydomonas reinhardtii is an accepted food ingredient in the United States of America (United States), the European Union, Singapore, and China. It can be consumed in unlimited quantities. As this alga is rich in nutrients, proteins, and rough polysaccharides and contains a balanced proportion of various amino acids, it is an excellent raw material for food production. Although various edible brown and green algae are available on the market, their color and strong grassy flavor have constrained their popularity among consumers, thereby limiting their application in food additives and animal feed. Methods Chlorophyll-deficient C. reinhardtii mutants were developed using atmospheric and room temperature plasma (ARTP) technology. Results A yellow-colored C. reinhardtii variant (A7S80) cultivated in dark conditions was isolated. This light-sensitive variant has a mutation in the chlM gene, and it can grow heterotrophically using acetate as a carbon source. Conclusion Compared to wild-type C. reinhardtii, A7S80 has significantly lower chlorophyll levels, reduced grassy flavor, and more diverse pigments, with considerable potential for commercial application in human and animal food production, as well as in pharmaceutical and cosmetic industries.